Optimal utilization of electrical energy from power plants based on final energy consumption using gravitational search algorithm - Montazeri, Z.; Niknam, T. (Електротехніка і електромеханіка, 2018)
Purpose. Energy consumption is a standard measure to evaluate the progress and quality of life in a country. When used properly
and logically it could be cause of progress in science, technology and welfare of the people in any country and otherwise
irreparable economic losses and economic gross recession would happen. And finally, the quantity of energy consumption per
GDP will increase day by day. Electrical energy, as the most prominent type of energy, is very important. In this article based on a
different approach, according to the final consumption of electric energy, a proper economic planning in order to supply
electrical energy is submitted. In this programming, the details of final energy consumption, will replace with the information of
power network, by considering the network efficiency and power plants. Operation of power plants is based on the energy
optimization entranced to a plant. By using the proposed method and gravitational search algorithm, the total cost of electrical
energy can be minimized. The results of simulation and numerical studies show better convergence of gravitational search
algorithm in comparison with other existing methods in this area. Цель. Энергопотребление является стандартной мерой для оценки прогресса и качества жизни в стране. Правильное и
обоснованное ее использование может привести к прогрессу в науке, технике и благосостоянии людей в любой стране, в
противном случае произойдут непоправимые экономические потери и падение валового внутреннего продукта. И,
наконец, количество потребленной энергии на единицу ВВП будет возрастать с каждым днем. Электрическая энергия,
как основной вид энергии, является весьма важной. В данной статье, основываясь на различных подходах, в
соответствии с конечным потреблением электрической энергии, представлено соответствующее экономическое
планирование подачи электроэнергии. При этом, подробности конечного потребления энергии заменяются
информацией о сети электроснабжения, учитывая эффективность сети и электростанций. Работа электростанций
основана на оптимизации энергии, производимой ею. Используя предложенный метод и алгоритм гравитационного
поиска, можно минимизировать общую стоимость электрической энергии. Результаты моделирования и численных
исследований показывают лучшую сходимость алгоритма гравитационного поиска по сравнению с другими
существующими методами в данной области.